Carbon capture utilization and storage in review: Sociotechnical implications for a carbon reliant world - McLaughlin, Hope (2023)
The decarbonization of industry and industrial systems is a pressing challenge given the relative lack of low-carbon options available for “hard to decarbonize” sectors such as steelmaking, cement manufacturing, and chemical production. Carbon capture utilization and storage (CCUS) represents a promising and crosscutting solution to this formidable problem. This review takes a systematic and sociotechnical perspective to examine how CCUS can support industrial decarbonization and relevant associated technical, economic, and social factors. This includes a focus on the energy and climate impacts of carbon emitting activities, the role, and options for CCUS in global responses to climate change, technical aspects of capture, transport, storage, and utilization, as well as policy implications and areas requiring further research. In doing so, the Review examines hundreds of published studies on the topic over the previous twenty years to offer a state-of-the-art investigation on technical options for capture (including direct air capture), transportation (including pipelines, ships, and rail), storage (including biotic and abiotic), and utilization (including enhanced oil recovery and biochar). The Review also investigates the evidence base within the literature on enablers and barriers to CCUS, policy mechanisms, and international frameworks as well as themes such as geopolitics, trade, and future research gaps. We conclude with insights about future CCUS pathways and sociotechnical systems dynamics.